1996
DOI: 10.1063/1.115682
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic modeling of microscopic processes during electron cyclotron resonance microwave plasma-assisted molecular beam epitaxial growth of GaN/GaAs-based heterostructures

Abstract: Microscopic growth processes associated with GaN/GaAs molecular beam epitaxy ͑MBE͒ are examined through the introduction of a first-order kinetic model. The model is applied to the electron cyclotron resonance microwave plasma-assisted MBE ͑ECR-MBE͒ growth of a set of ␦-GaN y As 1Ϫy /GaAs strained-layer superlattices that consist of nitrided GaAs monolayers separated by GaAs spacers, and that exhibit a strong decrease of y with increasing T over the range 540-580°C. This y͑T͒ dependence is quantitatively expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
7
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 5 publications
2
7
0
Order By: Relevance
“…The fraction of black regions is 4.45  0.05  10 -3 , which corresponds to only about (1/5) monolayer of GaN per deposited layer, rather than the full monolayer assumed earlier. 8 A similar fractional area of clusters is obtained in several large-scale images, with total area > 0.2 m 2 . High resolution x-ray diffraction data of these GaN/GaAs superlattices indicates an average superlattice lattice constant, 5.6499 Å, previously interpreted in terms of (continuous) monolayers of GaAs 0.79 N 0.21 embedded in 192 Å GaAs layers.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…The fraction of black regions is 4.45  0.05  10 -3 , which corresponds to only about (1/5) monolayer of GaN per deposited layer, rather than the full monolayer assumed earlier. 8 A similar fractional area of clusters is obtained in several large-scale images, with total area > 0.2 m 2 . High resolution x-ray diffraction data of these GaN/GaAs superlattices indicates an average superlattice lattice constant, 5.6499 Å, previously interpreted in terms of (continuous) monolayers of GaAs 0.79 N 0.21 embedded in 192 Å GaAs layers.…”
supporting
confidence: 68%
“…High resolution x-ray diffraction data of these GaN/GaAs superlattices indicates an average superlattice lattice constant, 5.6499 Å, previously interpreted in terms of (continuous) monolayers of GaAs 0.79 N 0.21 embedded in 192 Å GaAs layers. 8 With the knowledge of the fractional area of the clusters, we estimate a cluster lattice constant of 4.6  0.1 Å, similar to bulk GaN. Therefore, we conclude that the nitrided regions consist of pure GaN, as opposed to some alloy composition with 20%  30% N.…”
mentioning
confidence: 61%
“…[11][12][13] While a rough and relaxed surface morphology is typically found after a prolonged exposure of active nitrogen in most of nitridation studies reported to date, 10,11 Hauenstein et al 11 have recently shown by using reflection high-energy electron diffraction ͑RHEED͒ results that a specular, (3ϫ3)-ordered, and coherently strained GaN film ͑approximately one monolayer in thickness͒ can be formed on GaAs͑001͒ through limitedexposure surface nitridation. 9,10 Despite its importance for growing nitride materials and Ga(As 1Ϫx N x ) mixedanion alloys, very little has been known about the atomicscale nature of the nitridation process.…”
mentioning
confidence: 99%
“…Apparently, thick layers (>0.5 µm) of dilute GaAs 1-x N x (x ≤ 0.03) alloys have been produced by nitride growth, 4,5 and attempts to increase the nitrogen composition in the alloy using GaAs surface nitridation resulted in GaAs/GaN/GaAs thin-layer structures 6 and δ-GaAs 1-x N x /GaAs superlattices (0.04 ≤ × ≤0.33). 7,8 The identification of the nitride/arsenide structures as binary or ternary alloys has relied upon x-ray diffraction (XRD), which has spatial resolution of hundreds of µm and averages over many surface layers parallel to the interfaces. Similarly, cross-sectional transmission electron microscopy (XTEM) images may represent an average over many surface layers perpendicular to the interfaces of interest.…”
Section: Introductionmentioning
confidence: 99%